Evaluation of The Maki Method and Sonication for Diagnosing Catheter-Related Infections in ICU Patients with Long-Term Central Venous Catheters - Kumar, Chandan; Srividhya, S. (Journal of Neonatal Surgery, 2025)
Background: Central venous catheters (CVCs) are commonly used in clinical settings but are associated with the risk of catheter-related infections (CRIs), including catheter-related bloodstream infections (CRBSIs). The detection of catheter tip colonization is critical for diagnosing CRIs. This study aims to evaluate the effectiveness of the Maki semiquantitative method and sonication, both individually and in combination, for detecting catheter tip colonization and CRBSIs in ICU patients. Methods: We conducted a study involving 87 ICU patients with CVCs in place for at least 7 days, which were removed due to suspected CRIs. The diagnosis of CRI was based on the development of sepsis or fever, with the Sepsis-3 Consensus Criteria applied. Catheter tip samples were collected and analyzed using the Maki semiquantitative method and sonication, both separately and in combination. Blood cultures were not collected from patients. Statistical analysis was performed using chi-square tests, Mann-Whitney U tests, Cohen’s Kappa test, and receiver operating characteristic (ROC) curves to assess the diagnostic performance. Results: Of the 94 CVCs analyzed, 23 blood stream infections (BSIs) were identified, with 10 (43.5%) diagnosed as CRBSIs and 13 (56.5%) as bloodstream infections of unknown origin (BSIUOs). The Maki method identified 7 (50%) of the 14 cases of catheter tip colonization, while sonication detected 1 (7.1%) case independently. The combination of Maki and sonication detected 7 (50%) cases. For diagnosing CRBSIs, the Area Under the Curve (AUC) for the combined method was 98%, higher than Maki alone (79%). The combination of methods did not significantly outperform Maki alone for detecting CRBSIs (p=0.32). A false-negative rate of 1.1% was found with Maki and sonication for catheter tip colonization. Conclusion: The Maki method outperformed sonication for detecting both catheter tip colonization and CRBSIs in ICU patients with short-term CVCs. Sonication, although more effective for long-term colonization, did not significantly improve diagnostic performance when used in conjunction with Maki. This study emphasizes the importance of selecting appropriate diagnostic methods based on catheter duration and the patient population, with Maki being a reliable and efficient method for routine clinical diagnostics in ICU settings.